The impact of cyclic fuels on the formation and structure of soot - Salamanca, Maurin (2021)
This paper investigates the impact of cyclic fuels on the nanostructure, nucleation and overall production of soot in an n-heptane (C₇H₁₆) laminar coflow diffusion flame. The fuels selected to dope the n-heptane flame are cyclopentene (C₅H₈), cyclohexene (C₆H₁₀) and methylcyclohexane (C₇H₁₄). These fuels were chosen for their differences in their structure and sooting tendency. The flame structure was studied with Differential Mobility Spectrometry (DMS) for particle size distribution determination, two-colour ratio pyrometry to calculate the soot volume fraction and soot temperature. The soot nanostructure was investigated using Raman spectroscopy and high-resolution transmission electron microscopy (HRTEM). The addition of cyclic fuels was found to promote the formation of soot nanoparticles earlier in flames. In addition, the soot volume fraction was increased significantly by the addition of the cyclic fuels, especially by the addition of cyclopentene. The addition of 20% of cyclopentene increased the soot volume fraction by a factor of 2. HRTEM results suggest a significant influence of cyclopentene on the soot nanostructure; cyclopentene addition promotes the incorporation of five-membered rings (pentagonal rings) leading to highly curved fringes. This suggests cyclopentene could be used as a fuel to promote curvature in different carbonaceous materials to modify their properties.